Heat-resistant high-transmittance silk-screen printing ink and application thereof
Through the combination of benzene-free epoxy resin and anhydride curing agent and the application of solid anhydride curing agent, the problem of poor UV resistance of insulating glue under high temperature ultraviolet light conditions is solved, and the excellent heat and UV resistance of ink is achieved, and high light transmittance and good silk screen printing are maintained.
Patent Information
- Application Number
- CN202411414172.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-28
AI Technical Summary
The existing insulating glue has poor UV resistance under high temperature ultraviolet light conditions and is prone to yellowing. While improving UV resistance, it is difficult to take into account both silkscreen and heat resistance, and it is necessary to maintain high light transmittance.
The combination of benzene-free epoxy resin and anhydride curing agent is used to control the molar ratio of epoxy groups and anhydride groups within the range of 1: (1~0.4), and fully cure to improve the heat and UV resistance of the ink, and replace part of the filler with a solid anhydride curing agent to improve the thixotropy and light transmittance of the screen printing.
The excellent UV resistance and heat resistance of the ink are achieved, high light transmittance is maintained, and good silk screen printing is ensured, avoiding the decrease in light transmittance caused by the increase of filler.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic ink compositions, and in particular to a heat-resistant and highly transparent silk-screen printing ink and an application thereof. Background Art
[0002] The new generation of insulating glue used in the double-glass field is expected to be transparent and UV-resistant, which can also be used as protective glue on the front of the component. At present, the performance evaluation of insulating glue is mainly measured from the aspects of light transmittance, viscosity, full-plate coating warping, UV resistance, hardness, adhesion, etc. However, the UV resistance of insulating glue has always been poor, especially under high temperature conditions of light, it is easy to turn yellow, and the yellowing resistance is weak. If only the UV resistance is considered, the screen printing performance and heat resistance of the insulating glue will face challenges under the premise of meeting the UV resistance. As an excellent insulating glue, it should also have good light transmittance. Therefore, it is of great significance to comprehensively improve the UV resistance and heat resistance of the insulating glue, and the insulating glue has good screen printing and maintains high light transmittance. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a heat-resistant high-transmittance silk screen printing ink and its application.
[0004] In a first aspect of the present invention, the present invention provides a heat-resistant and highly transparent silk screen printing ink. According to an embodiment of the present invention, the ink comprises: A benzene ring-free epoxy resin, an anhydride curing agent, an accelerator, a filler and a solvent, wherein the molar ratio of the epoxy group in the benzene ring-free epoxy resin to the anhydride group in the anhydride curing agent is 1:(1-0.4).
[0005] According to the heat-resistant and highly transparent silk-screen printing ink of the above-mentioned embodiment of the present invention, the use of benzene ring-free epoxy resin can improve the UV resistance of the ink and avoid yellowing of the ink. However, the inventors found that if only the benzene ring-free epoxy resin is used to solve the UV resistance of the ink, a new problem will be introduced, that is, the heat resistance of the transparent silk-screen printing ink is not good. Therefore, the benzene ring-free epoxy resin and the acid anhydride curing agent used in this application are fully cured, thereby improving the heat resistance of the ink. In particular, the molar ratio of the epoxy group in the benzene ring-free epoxy resin to the anhydride group in the acid anhydride curing agent is controlled to be 1: (1~0.4), for example, the molar ratio is 1:1, 1:0.85, 1:0.6, 1:0.4, etc., or the range between any two of the above values, so that the benzene ring-free epoxy resin and the acid anhydride curing agent are fully cured, thereby improving the overall performance of the coating.
[0006] In addition, during the application of transparent insulating adhesive, it is necessary to balance the transmittance and screen printing yield. The insulating adhesive needs to have a high transmittance, which indicates that the filler content in the system is small, which will lead to too high a resin content in the coating, too high viscosity, and easy to cause the screen to stick to the screen. In addition, the filler in the coating has a thixotropic effect, so that the coating shape can continue to be maintained after screen printing, without collapse, edge expansion and other defects.
[0007] The curing agent used in this application is an anhydride curing agent. The anhydride curing agent has no benzene ring structure, which can further improve the yellowing resistance of the ink. In particular, the anhydride curing agent is used to not only have a curing effect, but the solid anhydride curing agent can also act as a filler in the early curing process of the coating, thereby improving the thixotropy of the ink system during the screen printing process. In the later curing process, the solid anhydride curing agent will melt and further cross-link with the epoxy resin to form a transparent coating, which has no effect on the light transmittance of the glue layer. The solid anhydride curing agent replaces the traditional part of the filler, which solves the problem of light transmittance reduction caused by adding too much filler for good screen printing, thereby maintaining excellent light transmittance of the ink. As a result, the ink has excellent UV resistance and heat resistance, good screen printing, and high light transmittance.
[0008] In some embodiments of the present invention, the benzene ring-free epoxy resin includes at least one of hydrogenated bisphenol A epoxy resin, aliphatic glycidyl ether resin, ester ring epoxy resin, silicone epoxy resin, and glycidyl amine resin.
[0009] In some embodiments of the present invention, the anhydride curing agent includes at least one of a solid anhydride curing agent or a liquid anhydride curing agent.
[0010] Preferably, the anhydride curing agent is selected from a solid anhydride curing agent. The inventors have found that the solid anhydride curing agent can also act as a filler during the early curing and coating setting process to improve the thixotropy of the ink system during the screen printing process. In the later curing process, the solid anhydride curing agent will melt and further cross-link with the epoxy resin to form a transparent coating, which has no effect on the light transmittance of the adhesive layer. The solid anhydride curing agent replaces the traditional part of the filler, which solves the problem of light transmittance reduction caused by adding too much filler to improve thixotropy for good screen printing, thereby maintaining excellent light transmittance of the ink.
[0011] In some embodiments of the present invention, the solid anhydride curing agent includes but is not limited to at least one of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, nadic anhydride, dodecyl succinic anhydride, methylcyclohexene tetracarboxylic anhydride, poly(methylenedianhydride), and modified maleic anhydride.
[0012] In some embodiments of the present invention, the liquid anhydride curing agent includes but is not limited to at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and methylnadic anhydride.
[0013] In some embodiments of the present invention, the particle size of the solid anhydride curing agent is 1 μm to 8 μm. For example, the particle size is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc., or a range between any two of the above values. The inventors have found that if the particle size of the solid anhydride curing agent is too small, the reaction probability of epoxy and curing agent at room temperature will increase, thereby shortening the shelf life. If the particle size of the solid anhydride curing agent is too large, screen blocking will occur.
[0014] In some embodiments of the present invention, the viscosity of the ink is 5Pa·s to 30Pa·s. For example, the viscosity is 5Pa·s, 10Pa·s, 15Pa·s, 20Pa·s, 25Pa·s, 30Pa·s, etc., or a range between any two of the above values. The inventors have found that when the viscosity of the ink is controlled within the above range, the screen printing yield can be improved, the printed pattern is clear, and there are no defects such as edge expansion.
[0015] In some embodiments of the present invention, the content of solvent in the ink is 0.5wt% to 20wt%. For example, the content of solvent is 0.5wt%, 2wt%, 5wt%, 8wt%, 10wt%, 13wt%, 15wt%, 18wt%, 20wt%, etc., or a range between any two of the above values.
[0016] In some embodiments of the present invention, the boiling point of the solvent is 180~220℃. The preferred solvent includes at least one of DBE, DPM, and tetramethylbenzene. The use of the above-mentioned high-boiling point solvent can reduce solvent volatilization during the screen printing process, and the viscosity parameters of the screen printing ink and other changes are small. The mass fraction of the solvent in the thermosetting ink is within the above range, and the viscosity of the system can be adjusted to adapt to the client's screen printing process. The low amount of solvent allows the scraper to quickly scrape back and forth across the screen during rapid screen printing, and a small amount of slow-drying solvent evaporates. After a small amount of high-boiling solvent evaporates, the effect on the change in coating viscosity is small, which matches the original screen printing process.
[0017] In some embodiments of the present invention, based on the total mass of the ink, the mass proportion of the accelerator is 0.5% to 5%. For example, the mass proportion of the accelerator is 0.5%, 1%, 2%, 3%, 4%, 5%, etc., or a range between any two of the above values.
[0018] In some embodiments of the present invention, the accelerator includes at least one of a tertiary amine accelerator, a carboxylic acid complex salt of a tertiary amine, a quaternary ammonium salt, a boron amine complex, an organic metal compound, and an acetylacetone metal complex.
[0019] As an example, the tertiary amine accelerator includes at least one of triethylamine (TEA), triethylhydroxylamine, benzyldimethylamine (BDMA), dimethylaminomethylphenol (DMPZ-10), tris(dimethylaminomethyl)phenol (DMP-30), and 2-ethyl-4-methylimidazole. The carboxylic acid complex salt of the tertiary amine includes at least one of R3N·HA and 2-ethylhexanoate (K-61B) of DMP-30. The quaternary ammonium salt includes R3NR'X. The boron amine complex includes BF3·NHR2. The metal organic compound includes at least one of zinc cyclohexaneate and zinc octoate. The acetylacetone metal complex includes a metal acetylacetone complex based on a transition or rare earth metal element and acetylacetone.
[0020] In some embodiments of the present invention, based on the total mass of the ink, the mass proportion of the filler is 0.5% to 10%. For example, the mass proportion of the filler is 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or a range between any two of the above values. The inventors found that by controlling the mass proportion of the filler within the above range, while ensuring good thixotropy of the coating, good silk screen printing, and non-stick screen, the pattern clarity and transmittance can be maintained between 85% and 90%.
[0021] In some embodiments of the present invention, the filler includes at least one of aerosil, silica powder, glass powder, barium sulfate, mica, and phosphor.
[0022] In some embodiments of the present invention, the ink further comprises an additive.
[0023] In some embodiments of the present invention, the auxiliary agent includes at least one of a defoaming agent, a leveling agent, and a dispersant.
[0024] As examples, the defoaming agent includes, but is not limited to, a polyether defoaming agent, a silicone defoaming agent, and a polyether-modified silicone defoaming agent.
[0025] As an example, the leveling agent includes, but is not limited to, a silicone leveling agent, an acrylic leveling agent, a fluorocarbon leveling agent, and a polyether leveling agent.
[0026] As examples, the dispersant includes, but is not limited to, anionic wetting and dispersing agents, cationic wetting and dispersing agents, and acrylate polymer dispersants.
[0027] In some embodiments of the present invention, based on the total mass of the ink, the mass proportion of the additive is 0.1% to 2%, for example, 0.1%, 0.3%, 0.5%, 0.7%, 1.0%, 1.3%, 1.5%, 1.8%, 2%, etc.
[0028] In a second aspect of the present invention, the present invention proposes the use of the above-mentioned heat-resistant and highly light-transmittance silk-screen printing ink in photovoltaic modules.
[0029] The present invention has at least the following technical effects: The present application uses a benzene ring-free epoxy resin to improve the UV resistance of the ink and avoid yellowing of the ink. The benzene ring-free epoxy resin and the anhydride curing agent are fully cured, thereby improving the heat resistance of the ink and ensuring good screen printing of the ink. In particular, the molar ratio of the epoxy group in the benzene ring-free epoxy resin to the anhydride group in the anhydride curing agent is controlled to be 1: (1~0.4), and the benzene ring-free epoxy resin and the anhydride curing agent are fully cured, thereby improving the overall performance of the coating. The use of a solid anhydride curing agent can not only improve the yellowing resistance of the ink, but also act as a filler to improve the thixotropy of the ink system during the screen printing process. It will melt during the curing process and has no effect on the light transmittance of the ink, thereby ensuring that the ink has good light transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is the wet film state diagram after ink screen printing; Figure 2 is a pattern after the ink is screen-printed and cured according to an embodiment of the present invention; Figure 3 This is the pattern after the ink of the comparative example of the present invention is screen-printed and cured. DETAILED DESCRIPTION
[0032] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0033] Example 1
[0034] The composition of heat-resistant and highly transparent screen printing ink is as follows: Benzene ring-free epoxy resin: hydrogenated bisphenol A epoxy resin DER331 (Dow), 100 parts by weight; Anhydride curing agent: 70 parts by weight of polyazelaic anhydride (Xia Chemical); The particle size of the polyazelaic anhydride is 5 μm, and the molar ratio of the epoxy group in the hydrogenated bisphenol A epoxy resin to the anhydride group in the polyazelaic anhydride is 1:0.85; Accelerator: 2-ethylhexanoate of DMP-30, based on the total mass of the ink, the mass proportion of the accelerator is 5%; Filler: gas silica, based on the total mass of ink, the mass of filler accounts for 3%; Solvent: DBE, the content of solvent in the ink is 10wt%; Defoaming agent: byk065, based on the total mass of ink, the mass proportion of defoaming agent is 0.5%.
[0035] The above materials were mixed evenly to prepare a heat-resistant and highly transparent silk-screen printing ink with a viscosity of 15 Pa·s.
[0036] Example 2
[0037] The difference between Example 2 and Example 1 is that the viscosity of the ink is 15 Pa·s by adjusting the added amounts of hydrogenated bisphenol A epoxy resin and polyazeoic anhydride, controlling the molar ratio of the epoxy groups in the hydrogenated bisphenol A epoxy resin to the anhydride groups in the polyazeoic anhydride to be 1:0.4, and adjusting the amount of the solvent.
[0038] Example 3
[0039] The difference between Example 3 and Example 1 is that the viscosity of the ink is 15 Pa·s by adjusting the added amounts of hydrogenated bisphenol A epoxy resin and polyazeoic anhydride, controlling the molar ratio of the epoxy groups in the hydrogenated bisphenol A epoxy resin to the anhydride groups in the polyazeoic anhydride to be 1:1, and adjusting the amount of the solvent.
[0040] Example 4
[0041] The difference between Example 4 and Example 1 is that the particle size of the polyazetadine anhydride is 1 μm.
[0042] Example 5
[0043] The difference between Example 5 and Example 1 is that the particle size of the polyazetadine anhydride is 3 μm.
[0044] Example 6
[0045] The difference between Example 6 and Example 1 is that the particle size of the polyazetadine anhydride is 8 μm.
[0046] Example 7
[0047] The composition of heat-resistant and highly transparent screen printing ink is as follows: Benzene-free epoxy resin: The mass of hydrogenated bisphenol A epoxy resin DER331 (Dow): the mass of propylene glycol triglycidyl ether (McLean) = 3:1,
[0048] Anhydride curing agent: The mass of polyazelaic anhydride (Xiahua Chemical): the mass of methyltetrahydrophthalic anhydride (McLean) = 1:1, the particle size of polyazelaic anhydride is 5μm,
[0049] The addition amount of the benzene ring-free epoxy resin and the anhydride curing agent is controlled so that the molar ratio of the epoxy group to the anhydride group is 1:0.85; Accelerator: 2-ethylhexanoate of DMP-30, based on the total mass of the ink, the mass proportion of the accelerator is 5%; Filler: gas silica, based on the total mass of ink, the mass of filler accounts for 3%; Solvent: DBE, the content of solvent in the ink is 15wt%; Defoaming agent: byk065, based on the total mass of ink, the mass proportion of defoaming agent is 0.5%.
[0050] The above materials were mixed evenly to prepare a heat-resistant and highly transparent silk-screen printing ink with a viscosity of 6 Pa·s.
[0051] Example 8
[0052] The composition of heat-resistant and highly transparent screen printing ink is as follows: Benzene-free epoxy resin: hydrogenated bisphenol A epoxy resin DER331 (Dow),
[0053] Anhydride curing agent: polyazelaic anhydride (Xia Chemical), the particle size of polyazelaic anhydride is 5μm, and the amount of benzene ring-free epoxy resin and anhydride curing agent added is controlled so that the molar ratio of the epoxy group in the hydrogenated bisphenol A epoxy resin to the anhydride group in the polyazelaic anhydride is 1:0.85; Accelerator: 2-ethylhexanoate of DMP-30, based on the total mass of the ink, the mass proportion of the accelerator is 5%; Filler: Based on the total mass of ink, silica 5%, barium sulfate 5%; Solvent: DBE, the content of solvent in the ink is 0.5wt%; Defoaming agent: byk065, based on the total mass of ink, the mass proportion of defoaming agent is 0.5%.
[0054] The above materials are mixed evenly to prepare a heat-resistant and highly transparent screen printing ink having a viscosity of 30 Pa·s.
[0055] Comparative Example 1
[0056] The difference between Comparative Example 1 and Example 1 is that the anhydride curing agent in Comparative Example 1 is liquid, and the anhydride curing agent is methyltetrahydrophthalic anhydride (McLean).
[0057] Comparative Example 2
[0058] The difference between Comparative Example 2 and Example 1 is that the molar ratio of the epoxy group in the bisphenol A epoxy resin to the anhydride group in the tetrahydrophthalic anhydride is 1:0.3.
[0059] Comparative Example 3
[0060] The difference between Comparative Example 3 and Example 1 is that the molar ratio of the epoxy group in the bisphenol A epoxy resin to the anhydride group in the tetrahydrophthalic anhydride is 1:1.2.
[0061] The properties of the inks prepared in the examples and comparative examples were measured, and the specific method is as follows: Thermal decomposition temperature: tested according to GB / T37631-2019.
[0062] Hardness: Tested according to GB / T6739-2006.
[0063] Yellowing index: tested according to GB2409-80.
[0064] Peel strength with EVA: Peel strength test is carried out according to GB / T2790.
[0065] Light transmittance: tested according to HG / T3331-1985.
[0066] Wet heat test: After the adhesive is printed and completely cured, the materials are laminated in the order of glass / adhesive film / battery / adhesive film / glass. A simulated laminated small component is made and placed in an environmental test chamber. According to the provisions of IEC 61215-2005, accelerated aging is carried out in a temperature and humidity chamber at 85℃±2℃ and humidity (85±5)%RH. The yellowing index (△YI) and peel strength of the sample after aging for 1000h are recorded.
[0067] UV aging test: After the glue is printed and fully cured, it is laminated in the order of glass / film / battery / film / glass. A simulated laminated small component is made and placed in an environmental test chamber. Test conditions: temperature (60±5)C, UV radiation in the range of 280nm~400nm reaches 120kWh / m 2 (The UV radiation with a wavelength of 280nm to 320nm accounts for 3%~10% of the total UV radiation). The yellowing index test is performed on the laminate after UV120 test at a light intensity of 400-700lux.
[0068] Screen printing performance: The coating is printed on the surface of the battery cell substrate with a 200-mesh screen. After printing, the surface is smooth without missing prints, bubbles, wire drawing, burrs, or overflow.
[0069] The performance test results of the inks prepared in the examples and comparative examples are shown in Table 1.
[0070] Table 1
[0071] As can be seen from Table 1, by controlling the molar ratio of the epoxy group in the benzene ring-free epoxy resin to the anhydride group in the solid acid anhydride curing agent to be 1: (1~0.4), the benzene ring-free epoxy resin and the solid acid anhydride curing agent are fully cured, thereby improving the overall performance of the coating. The use of solid acid anhydride curing agent can not only improve the yellowing resistance of the ink, but also act as a filler to improve the thixotropy of the ink system during the screen printing process. It will melt during the curing process and has no effect on the light transmittance of the ink, thereby ensuring that the ink has good light transmittance. However, when only liquid acid anhydride is used and the amount of filler is low, the coating has good fluidity after screen printing, severe collapse, and severe pattern expansion. Specifically, the wet film state of the ink after screen printing is as follows Figure 1 As shown, the pattern obtained after the ink screen printing of the embodiment of the present application is cured is consistent with the pattern of the wet film before curing, such as Figure 2 As shown. However, the pattern obtained after the comparative ink screen printing is cured has a serious expansion and cannot maintain a rectangular pattern. This is mainly because the small molecular resin causes the pattern to seep oil, such as Figure 3 shown.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A heat-resistant and highly transparent silk screen printing ink, characterized in that: include: A benzene ring-free epoxy resin, an anhydride curing agent, an accelerator, a filler and a solvent, wherein the molar ratio of the epoxy group in the benzene ring-free epoxy resin to the anhydride group in the anhydride curing agent is 1:(1-0.4).
2. The ink according to claim 1, characterized in that: The viscosity of the ink is 5 Pa·s to 30 Pa·s; And / or, the content of the solvent in the ink is 0.5wt%~20wt%.
3. The ink according to claim 1 or 2, characterized in that: The benzene ring-free epoxy resin includes at least one of hydrogenated bisphenol A epoxy resin, aliphatic glycidyl ether resin, ester ring epoxy resin, silicone epoxy resin, and glycidyl amine resin.
4. The ink according to claim 1 or 2, characterized in that: The acid anhydride curing agent includes at least one of a solid acid anhydride curing agent and a liquid acid anhydride curing agent, and the solid acid anhydride curing agent is preferred.
5. The ink according to claim 4, characterized in that: The particle size of the solid anhydride curing agent is 1 μm to 8 μm; And / or, the solid acid anhydride curing agent includes at least one of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, nadic anhydride, dodecyl succinic anhydride, methylcyclohexene tetracarboxylic anhydride, poly(methylenedianhydride), and modified maleic anhydride; And / or, the liquid anhydride curing agent includes at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and methylnadic anhydride.
6. The ink according to claim 1 or 2, characterized in that: Based on the total mass of the ink, the mass proportion of the accelerator is 0.5% to 5%; And / or, the accelerator includes at least one of a carboxylate complex salt of a tertiary amine, a quaternary ammonium salt, a boron amine complex, an organic metal compound, and an acetylacetone metal complex.
7. The ink according to claim 1 or 2, characterized in that: Based on the total mass of the ink, the mass proportion of the filler is 0.5% to 10%; And / or, the filler includes at least one of aerosil, silica powder, glass powder, barium sulfate, mica, and fluorescent powder.
8. The ink according to claim 1 or 2, characterized in that: The ink also includes an additive; Preferably, the auxiliary agent includes at least one of a defoamer, a leveling agent, and a dispersant; And / or, based on the total mass of the ink, the mass proportion of the auxiliary agent is 0.1% to 2%.
9. The ink according to claim 1 or 2, characterized in that: The boiling point of the solvent is 180-220°C; Preferably, the solvent includes at least one of DBE, DPM and tetramethylbenzene.
10. Use of the heat-resistant and highly transparent silk-screen printing ink according to any one of claims 1 to 9 in photovoltaic modules.